Gold adsorption and elution in thiosulfate leaching system using functionalized magnetic nanoparticles - Ilankoon, N.; Oraby, Elsayed; Eksteen, Jacques; Aldrich, C. (2019)
© IMPC 2018 - 29th International Mineral Processing Congress. All rights reserved. The use of thiosulfate as an alternative lixiviant for cyanide to treat complex refractory ores followed by the use of ion exchange resins (IX resins) for gold recovery has become an industrial reality. In this study, polyethylenimine (PEI) coated iron oxide magnetic nanoparticles (MNPs) were used to recover gold from the leaching solutions that consist of calcium thiosulfate, copper and gold. The gold loaded MNPs were easily separated from the solution using an external magnetic field. Proposing a novel adsorbent with characteristically easy solid-liquid separation, to recover gold from synthetic thiosulfate leaching solutions and gold elution and reuse of MNPs were the main objectives of this study. Adsorption isotherm studies revealed that the data fitted both Langmuir and Freundlich isotherm models equally well. The maximum adsorption capacity was 18.5 mg/g at pH 8 and 50C. According to thermodynamic studies the physisorption process was exothermic and spontaneous. Gold and copper elution, and the regeneration and reuse of the nanoparticles were investigated and promising results were obtained. Different elution systems comprising sulfites, chlorides, glycine, EDTA (ethylenediaminetetraacetic acid) and sodium hydroxide were considered. Among them, EDTA for copper elution and NaOH for gold elution were the most efficient eluants. Regeneration and reuse studies revealed that the MNPs can be used for several cycles without significant performance loss.